PTFE Based Multilayer Micro-Coatings for Aluminum AlMg3 Forms Used in Tire Production - Novotny, Jan; Michna, Stefan; Hren, Iryna; Cais, Jaromir; Lysonkova, Irena; Svorcik, Vaclav (Coatings (Basel), 2021)
The basic prerequisite for obtaining the coating of good quality is the production of a layer without the occurrence of surface defects. A possible solution to the occurrence of defects on the functional surface of the form is the application of a polytetrafluoroethylene (PTFE)-based coating. The coating helps to reduce surface roughness and “smooth” defects like pores and micro-shrinkage. For this reason, a new type and methodology of the coating were prepared to achieve more production cycles between the individual cleaning processes during the production of a tire. The subject of the study was the analysis of surface-applied micro-coatings, including the analysis of chemical composition by using energy-dispersive X-ray (EDX) and microstructure in the area of coatings. Detailed microstructural characterization of Alfipas 7818 and Alfiflon 39 and its imaging of surface structures were studied using atomic force microscopy. To examine the surface layer of the coatings, metallographic specimens of cross-sections (by means of a mold) were prepared and examined by light and electron microscopy. This new multilayer micro-coating with a thickness of 20–25 μm has been found to prevent form contamination during tire production and to extend production cycles by 200–400% between process cleanings. This finding was actually tested in the production of tires in the environment of a large manufacturing company.